Markets, Minds, and Money : Why America Leads the World in University Research - Urquiola, Miguel (Harvard University Press, 2020)
Free markets made US universities world leaders in research. Economist Miguel Urquiola argues that in the late nineteenth century, entrepreneurial universities saw they could meet the industrializing country's demand for expertise. They moved away from religiously inspired teaching, and market dynamics allowed them to surpass European competitors.